Functional Swallowing Units (FSUs) as organs-at-risk for radiotherapy. PART 1: Physiology and anatomy. (January 2019) - Gawryszuk, Agata; Bijl, Hendrik P.; Holwerda, Monique; Halmos, Gyorgy B.; Wedman, Jan; Witjes, Max J.H.; van der Vliet, Anton M.; Dorgelo, Bart; Langendijk, Johannes A.
Highlights: Hyolaryngeal Elevation and Tongue Base Retraction are crucial swallowing components. Additional swallowing structures are defined based on swallowing physiology. Swallowing sparing strategies should probably reach beyond pharyngeal constrictors. Abstract: Background and purpose: When optimising radiotherapy treatments today, the pharyngeal constrictor muscles and the larynx are usually regarded as the swallowing organs at risk (SWOARs). The purpose of this study was to identify and describe additional, previously undefined groups of muscles (functional units) involved in crucial components of swallowing (hyolaryngeal elevation (HLE), tongue base retraction (TBR) and tongue motion), and to emphasise their relevance in radiation-induced dysphagia. Material and methods: Based on available literature on human anatomy and swallowing physiology, the functional units of muscles involved in HLE, TBR and tongue motion have been identified and described. Results and conclusion: Functional swallowing units (FSUs) were defined as groups of swallowing muscles sharing their function, that are in close proximity to each other. Seven FSUs involved in HLE, TBR and tongue motion were identified: floor of mouth, thyrohyoid muscles, posterior digastric/stylohyoid muscles complex, longitudinal pharyngeal muscles, hyoglossus/styloglossus muscles complex, genioglossus muscles, intrinsic tongue muscles. The swallowing physiology and anatomy of the FSUs described in this paper will lead to a greater understanding of radiation-induced dysphagia mechanisms and, consequently, to an improvement in the development of swallowing sparing strategies. This article (PART 1) serves as the theoretical foundation for a subsequent article (PART 2), which provides detailed delineation guidelines for FSUs.